Cloud-enabled data sharing model - Hung, Nguyen Thanh. (2013)
Database-as-a-Service is becoming more and more popular for many organizations. Storing data on the cloud can significantly reduce costs in terms of maintenance costs and initial investment costs. But due to data privacy and security concerns, many companies are still reluctant to use outsourced database service. In this paper, we present a solution to protect data privacy on the cloud, at the same time, allowing multiple users accessing the shared database with security assurance.